Deep nature play : a guide to wholeness, aliveness, creativity, and inspired learning - Cornell, Joseph Bharat (Nevada City, California : Crystal Clarity Publishers, 2017)
When absorbed in deep play our sensory awareness is heightened, we become immersed in the present moment and feel intensely alert and alive. Because play is fun and rewarding, we operate at the peak of our mental and physical capacity. Let Joseph Cornell, one of the world's most popular nature educators, empower you with the tools to maximize play, and transform it from mere entertainment into a doorway to enhanced living, creativity, and concentration.
Deep Nature Play; Contents; Foreword; An Introductory Story -- 1. Play Is Universal -- 2. Play Is Innate and Integral to Learning -- 3. A Positive Learning Experience Is Essential -- 4. Play Energizes Us -- 5. Play Unites Us with Others -- 6. Play Activates the Whole Person -- 7. Creativity Is the Heart of Play -- 8. Attunement: The Secret of Creativity -- 9. How Play Frees Your Creative Nature -- 10. Mindful Play -- 11. Play Is for Everyone -- 12. Converting Play into Deep Play; The Flow Learning"!Process -- 13. How You Can Play More Deeply -- 14. Four Deep Nature Play Games -- Camera -- Sound Map. Interview with Nature Vertical Poem -- Appendix: Meditation -- Notes -- Photographer Credits.
Includes index.
Keywords: LEISURE -- PHILOSOPHY